Organizational Culture and Personality Influence on Employee Motivation and Performance at PT Jasa Raharja East Kalimantan Branch - Paschal Muhammad Reza; Sri Mintarti; Doddy Adhimursandi (Journal of Social Science, 2022)
In this digital era, it is essential for a company to consistently grow in order to compete and meet the expectations of stockholders and stakeholders. Achieving this requires good performance and constantly sustainably making improvements and development. Employee performance can be influenced by organizational culture, personality, and motivation, either directly or indirectly. Organizational culture is one factor that influences motivation, and personality can also influence motivation, which ultimately affects employee performance. This study aims to analyze the influence of organizational culture, personality, and motivation on employee performance. This research sample is an employee of PT Jasa Raharja East Kalimantan Branch. Data analysis using SEM-PLS. The results showed a positive and significant influence of organizational culture and personality on motivation, motivation to employee performance, and organizational culture and personality to employee performance.